Non-resonant 3D Elliptical Vibration Cutting Induced Submicron Grating Coloring - Chen, Jianzhong; Lu, Mingming; Lin, Jieqiong; Zhou, Jiakang; Fu, Xifeng; Zhou, Xiaoqin (International journal of precision engineering and manufacturing, 2021)
Surface Submicron grating manufacturing has broad application prospects, which has also been the subject of intensive research and development by scholars with many efforts. In this paper, a grating coloring manufacturing method is proposed based on three-dimensional elliptical vibration cutting and non-resonant piezoelectric actuator. Based on the mechanism of elliptical motion, an effective cutting depth model was established. Nonlinear interaction of machining parameters (overlap rate, nominal cutting speed, vibration frequency) on the geometry of the grating were analyzed and controllable modulation model of grating geometry was established. The geometrical dimensions of the grating were predicted and grooved experiments were performed on brass and aluminum surfaces. A set of angle-adjustable detection device was designed independently to check the diffraction quality of the grating. The quantitative experimental results show that grating distances of copper and aluminum rods are 752 nm and 684 nm, respectively. The average width of the aluminum rod overall grating is 764 nm, the accuracy error is 9.25%. In addition, aluminum rod gratings can diffract red light at non-specific angles, which is more effective at viewing angle of 70°. The experimental results are in agreement with the theory which have positive significance for expanding the functional surface.